Five nights at Freddy's Fazbear frights. The fourth closet: the graphic novel - Cawthon, Scott, 1971-; Hastings, Chris, 1983-; Breed-Wrisley, Kira (Cawthon, Scott, 1971- Five nights at Freddy's. Fazbear frights, 2022)
"What really happened to Charlie? It's the question that John can't seem to shake, along with the nightmares of Charlie's seeming death and miraculous reappearance. John just wants to forget the whole terrifying saga of Freddy Fazbear's Pizza, but the past isn't so easily buried. Meanwhile, there's a new animatronic pizzeria opening in Hurricane, along with a new rash of kidnappings that feel all too familiar. Bound together by their childhood loss, John reluctantly teams up with Jessica, Marla and Carlton to solve the case and find the missing children. Along the way, they'll unravel the twisted mysteryof what really happened to Charlie, and the haunting legacyof her father's creations"--Back cover.